2006
DOI: 10.1097/01.aids.0000218556.36661.47
|View full text |Cite
|
Sign up to set email alerts
|

The costs and benefits of private sector provision of treatment to HIV-infected employees in Kampala, Uganda

Abstract: A 'hybrid' intervention combining CTX prophylaxis followed by HAART would generate savings to a Ugandan company. Governments and other donors may find opportunities to share costs with the private sector as part of their phase-in strategy for antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…We estimated net DALYs by subtracting the increase in DALYs due to adverse events from the reduction in DALYs due to HIA. We calculated the reduction in DALYs for HIV by multiplying HIA by previously reported discounted DALY changes with ART (ten DALYs) and without (21 DALYs), assuming 50% on ART [45]. For increases in DALYs, we estimated the frequency and duration of adverse events from the OF RCT.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated net DALYs by subtracting the increase in DALYs due to adverse events from the reduction in DALYs due to HIA. We calculated the reduction in DALYs for HIV by multiplying HIA by previously reported discounted DALY changes with ART (ten DALYs) and without (21 DALYs), assuming 50% on ART [45]. For increases in DALYs, we estimated the frequency and duration of adverse events from the OF RCT.…”
Section: Methodsmentioning
confidence: 99%
“…We used our model published elsewhere to estimate health benefits after the first two years. 26 Mortality for individuals taking second-line HAART, derived from a study conducted in a South-African township, is set at 1.9% per month. 13 No third-line regimen is available.…”
Section: Deaths Averted-basedmentioning
confidence: 99%
“…Using estimates from a Markov model published previously on disease progression in a simulated Ugandan cohort, we found that each HIV infection prevented averted 7.2 DALYs. 26 This assumes that all of those who would have become infected would have received ART. 32 The DREAM cohort study (with ART) in Mozambique found a pediatric seroconversion rate of 5.5% at 12 months of age.…”
Section: Deaths Averted-basedmentioning
confidence: 99%
“…Treatment with ART was estimated to avert 7.3 discounted DALYs among HIV-infected individuals who survived >16 weeks. This value was drawn from the same Zambian analysis used to estimate treatment costs, and it was obtained by comparing deaths in the Zambian ART program with deaths observed in a prior, well-characterized home-based AIDS care (HBAC) cohort of 466 HIV-infected patients not receiving ART in Tororo District, Uganda, adjusted for differences in CD4+ T-cell counts and sex distribution between groups [16,19,24,25]. …”
Section: Methodsmentioning
confidence: 99%